The magnitude of early response to methotrexate therapy predicts long-term outcome of patients with juvenile idiopathic arthritis. Issue 3 (27th July 2007) - Bartoli, M; Tarò, M; Magni-Manzoni, S; Pistorio, A; Traverso, F; Viola, S; Magnani, A; Gasparini, C; Martini, A; Ravelli, A
Abstract : Objective: To investigate the relationship between the magnitude of clinical response in the first 6 months of methotrexate (MTX) therapy and long-term outcome in children with juvenile idiopathic arthritis (JIA). Methods: The clinical charts of 125 JIA patients who were started with MTX and then followed for at least 5 years were reviewed. Based on the level of American College of Rheumatology (ACR) Pediatric response at 6 months, patients were divided in four mutually exclusive groups: (1) non-responders, (2) responders at 30%, (3) responders at 50%, and (4) responders at 70%. The long-term outcome in each response group was evaluated by calculating the percentage change in active and restricted joint counts from baseline to 1, 2 and 5 years and the frequency of inactive disease at 5 years. Results: At 6 months, 42 patients were classified as non-responders, 24 as 30% responders, 26 as 50% responders, and 33 as 70% responders. Patients who had achieved a 70% response showed a significantly greater percentage improvement in active joint count between baseline to 5 years compared with non-responders and 30% responders, and a significantly greater percentage improvement in restricted joint count between baseline to 5 years compared with 30% responders. The 70% responders also had a greater frequency of inactive disease at 5 years compared with 30% responders, Conclusions: Our results show that the achievement of an ACR Pediatric 70 response at 6 months after start of MTX therapy predicts a more favorable long-term outcome of patients with JIA.